Strategi Pengembangan Sistem Keamanan Terpadu untuk Melindungi Sistem Operasi Windows dari Ancaman Cyber - Sarvina Sari Ahmad Fadil (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
The Windows operating system has become one of the main targets for cyber attackers because of its popularity among computer users. Therefore, developing an effective integrated security system is essential to protect the Windows operating system from various cyber threats. This journal discusses integrated security system development strategies that include the use of encryption technology, firewalls, malware scanning, system updates, and user awareness. Apart from that, this journal also discusses the implementation of an integrated security strategy to protect the Windows operating system from increasingly complex cyber attacks. The goal of this journal is to provide strategic guidance for IT security professionals and researchers in developing an effective integrated security system to protect the Windows operating system from ever-evolving cyber threats.